William James’s Assessment of Nihilism as a Psychological Phenomenon - Jon Stewart (Phainomena)
The present article examines the contribution to the problem of nihilism found in the American philosopher and psychologist William James, specifically in his essay “Is Life Worth Living?” from 1896 and the chapter “The Sick Soul” from his The Varieties of Religious Experience from 1902. At the age of 27, James suffered a period of intense depression that lasted from the fall of 1869 until the spring of 1870. This experience shaped his views on nihilism. The present article argues that James’s proposed solution to the problem of nihilism, although formulated rather differently, is in essence the same as that of Jean Paul and the Danish thinker Poul Martin Møller. James’s originality can be found in his treatment of the issue as a psychological problem.